Penerapan Service Excellence Sebagai Upaya Peningkatan Kualitas Layanan Humas Pemerintah Kota Surabaya (Studi Pada Koridor Co-Working Space) - Aisyah Nila Tsamara; Jaka Nugraha (Universitas Negeri Surabaya, 2020)
In this increasingly advanced era, the more needs and broad selection of jobs that can be accessed by all levels of society, the obligation to work in balancing humas needs in unaviodable. Therefore, there are many ways in which companies provide their best services, one of which is by changing the work system like at home, but in a unique way Hibbert. Previously Co-working Space was known as SOHO (Small Ofiice Home Office) a place for freelancers if they were bored working at home. The same thing is also felt by the people of Surabaya, which have increasingly established the establishment of Co-working Space from the private sector. The emergence of problems that became the basis of the Surabaya Citu Government established the Co-working Space Corridor because startup founders, freelancers, and creators who could not continue renting tp private companies. This study aims to describe the application of service excellence as an effort to improve the quality of public relations services of the Surabaya City Government. This type of research is descriptive with a qualitative approach, the subjects in this study were the Head of Information Services Sub-Section, Information Service Section Staff, and Corridor employees. And the object of his research is the application of service excellence as an effort to improve the quality of public relations in the city government. Data collection techniques used were interviews, observation, adn documentation. Data analysys techniques used consist of data reduction, data presentation anad drawing conclusions with data validity techniques using source triangulation. The result showes that the application of the concept of service excellence in the corridor carried out by the Public Relations has been running well and maximally and in accordance with the objective of the Surabaya City government by taking into account the values of the Co-working Space: 1) community; 2) accessibility; 3) collaboration; 4) communication; 5) openness; and 6) creativity.